The Role of Islamic Religious Education Teachers in Instilling Spiritual Intelligence in Students of SDN 006 Bontang Utara - Janawati; Amir Patintingan; Muhammad Naim; Suredah Hamid (CV. Edujavare Publishing, 2026)
Spiritual intelligence is essential to be cultivated in students from an early age, as external influences may weaken the inner dimensions of children. Islamic Religious Education (PAI) teachers carry professional and moral responsibilities in forming students' spiritual intelligence. This study aims to describe the role of PAI teachers in instilling spiritual intelligence, analyze the strategies employed, and identify supporting and inhibiting factors at SDN 006 Bontang Utara. The study employs a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and document analysis. Data analysis followed the steps of data reduction, data display, and conclusion drawing, with validity verified through source and technique triangulation. The findings reveal that PAI teachers play a strategic role as role models, prayer mentors, spiritual motivators, organizers of religious activities, and communicators with parents. Strategies implemented include religious practice routines, storytelling, self-reflection, moral reinforcement, and collaboration among teachers and parents. Key supporting factors are teacher role modeling, school religious culture, and consistent religious habituation, while inhibiting factors include digital environment influence, limited PAI time, and insufficient spiritual guidance at home. These findings emphasize that developing spiritual intelligence requires continuous, structured, and comprehensive synergy among teachers, students, families, and the social environment.